2010
DOI: 10.1016/j.jus.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of contrast-enhanced ultrasonography in the characterization of ovarian tumors

Abstract: KEYWORDSAdnexal masses; Contrast-enhanced ultrasound; Ovarian cancer.Abstract Introduction: Vascularity influences the characteristics of gynecologic tumors observed with direct imaging techniques that reveal the macrovascular component of these lesions (color and power Doppler) and with indirect imaging involving the administration of contrast agents to examine the microcirculation and interstitial perfusion (contrast-enhanced computed tomography [CT] and magnetic resonance [MR] imaging). The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The contrast enhancement variables such as peak intensity, area under the intensity curve (AUC), time to peak (TTP), sharpness and half wash-out time were studied by Testa et al and Fleischer et al [19], [21], in which a second-generation contrast agent and low-MI CEUS were used. They found that AUC and peak values were highest in the malignant tumors and TTP values were similar in the benign and malignant tumors while a study by Sconfienza et al [20]. They found that TTP performed better than the other parameters.…”
Section: Discussionmentioning
confidence: 87%
“…The contrast enhancement variables such as peak intensity, area under the intensity curve (AUC), time to peak (TTP), sharpness and half wash-out time were studied by Testa et al and Fleischer et al [19], [21], in which a second-generation contrast agent and low-MI CEUS were used. They found that AUC and peak values were highest in the malignant tumors and TTP values were similar in the benign and malignant tumors while a study by Sconfienza et al [20]. They found that TTP performed better than the other parameters.…”
Section: Discussionmentioning
confidence: 87%
“…After screening titles and abstracts, a further 55 were excluded. After examination of the full text of the remaining 48 candidate studies, a further 34 were excluded, leaving 14 articles considered as being eligible for the systematic review. Three of these were not eligible for meta‐analysis due to missing sensitivity, specificity, accuracy or correlation values; thus, 11 studies were eligible for the meta‐analysis according to our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The I 2 values for sensitivity, specificity and DOR were 38.3%, 31.7% and 48.4%, respectively, indicating moderate heterogeneity for all three. The conclusions from three studies that examined CE‐US but were not included in the quantitative analysis were also assessed (data not shown); all three suggested that CE‐US is useful for discriminating benign from malignant ovarian tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Although the final diagnosis of ovarian masses is based on histology, preoperative differentiation of benign and malignant lesions is essential for decisions on the timing and technical characteristics of the surgery. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%